Eating behaviors as predictors of weight loss in a 6 month weight loss intervention. (2nd July 2013) - Batra, Payal; Das, Sai Krupa; Salinardi, Taylor; Robinson, Lisa; Saltzman, Edward; Scott, Tammy; Pittas, Anastassios G.; Roberts, Susan B.
Abstract : Objective: To examine associations between eating behavior constructs and weight loss (WL) in a 6‐month WL intervention in worksites. Design and Methods: A cluster‐randomized controlled trial of a group behavioral WL intervention versus wait‐listed control was conducted at four worksites. Measures included body weight and the eating behavior constructs restraint, disinhibition, hunger, and their sub‐constructs. Rates of intervention meeting attendance and weight self‐monitoring were also quantified. Results: WL was greater in intervention participants than controls (Δ I = −8.1±6.8 kg, Δ C = +0.9±3.6 kg, P <0.001). Between‐group analyses showed that the intervention was associated with increased restraint (Δ I = 5.43±4.25, Δ C = 0.29±3.80, P <0.001), decreased disinhibition (Δ I = −2.5±3.63, Δ C = 0.66±1.85, P < 0.001) and decreased hunger (Δ I = −2.79±3.13, Δ C = 0.56±2.63, P < 0.001), and changes in all eating behavior subscales. Greater WL in intervention participants was correlated with higher baseline hunger ( r = −0.25, P = 0.03), increased restraint ( r = −0.35, P =0.001), decreased disinhibition ( r = 0.26, P = 0.02), and decreased hunger ( r = 0.36, P = 0.001). However, in a multiple regression model including rates of meeting attendance and self‐monitoring, decreased hunger was the only eating behavior change that predicted weight loss ( R 2 =0.57, P <0.001). Conclusion: Decreased hunger was the strongest predictor of WL in this intervention with relatively high mean WL. Further studies are needed to confirm the central role of hunger management in successful WL.